Pengaruh Manajemen Laba Terhadap retun Saham pada Perusahaan yang Diaudit KAP Big 5 dan KAP Non Big 5 - ardiati, Aloysia yanti (The Indonesian Journal of Accounting Research, 2005)
This study examines whether a relation exists between audit quality and earnings management. Accrual based earnings is considered superior to cash flows. Accruals let managers communicate their private and inside information and thereby improve the ability of earnings to reflect underlying economic value. Auditing plays an important role in mitigating these agency costs by constraining opportunistic management of accruals. Earnings management is proxied by discretionary accruals which are estimated using cross-sectional version of Jones (1991) model. The findings of this study indicate that the effect of earnings management on stock returns is greater for firms audited by Big 5 auditors than audited by non-Big 5 auditors.